2001
DOI: 10.1002/ecja.1071
|View full text |Cite
|
Sign up to set email alerts
|

Coded pulse signal subsurface radar

Abstract: SUMMARYSubsurface radar to detect buried objects from the ground surface by using electromagnetic waves has been used widely for detection of buried pipes since a shallow subsurface zone of up to 2 to 3 m can be visualized with high resolution at high speed. On the other hand, deeper subsurface detection is required in searching for archaeological ruins. In this paper, a delay correlation-type subsurface radar using monocycle pulse signals modulated by M-sequence codes is proposed with a view to expanding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Narayanan et al demonstrated the performance of the random noise radar and applied it to locate buried targets [36,37]. Tomizawa et al proposed a random signal radar design based on M-sequence coded pulses [38], and the system can enhance the signal-to-noise ratio (SNR) and increase the detection range [39].…”
Section: Introductionmentioning
confidence: 99%
“…Narayanan et al demonstrated the performance of the random noise radar and applied it to locate buried targets [36,37]. Tomizawa et al proposed a random signal radar design based on M-sequence coded pulses [38], and the system can enhance the signal-to-noise ratio (SNR) and increase the detection range [39].…”
Section: Introductionmentioning
confidence: 99%